2005
DOI: 10.1021/jm050186i
|View full text |Cite
|
Sign up to set email alerts
|

[N-Ethyl- and [N,N‘-Diethyl-1,2-bis(2,6-difluoro-3-hydroxyphenyl)- ethylenediamine]dichloroplatinum(II):  Structure and Cytotoxic/Estrogenic Activity in Breast Cancer Cells

Abstract: N-Ethyl and N,N'-diethyl derivatives (erythro- and threo-2-PtCl2; meso- and D,L-3-PtCl2) of [meso- and [D,L-1,2-bis(2,6-difluoro-3-hydroxyphenyl)ethylenediamine]dichloroplatinum(II) (meso- and D,L-1-PtCl2) were synthesized and tested for cytotoxicity on the estrogen receptor-positive (ER+) human MCF-7 breast cancer cell line. In this test, only D,L-1-PtCl2 and threo-2-PtCl2 showed strong cytotoxic properties. This revealed the existence of at least one NH2 fragment as a prerequisite for antitumor activity. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Optimization of the alkyl substituents on the nitrogens afforded ligands with relatively high RBA values (up to 20.88%) in the competitive (to estradiol) calf uterus estrogen receptor binding assay but coordination to platinum(II) reduced the affinity to the ER drastically (RBA values 0.1 to 0.5%) [43]. Surprisingly, this did not lead to substantial changes in the estrogenic potency of the substances in the mouse uterine weight test.…”
Section: Development Of Hormonally Active [12-diarylethylenediamine]mentioning
confidence: 97%
See 1 more Smart Citation
“…Optimization of the alkyl substituents on the nitrogens afforded ligands with relatively high RBA values (up to 20.88%) in the competitive (to estradiol) calf uterus estrogen receptor binding assay but coordination to platinum(II) reduced the affinity to the ER drastically (RBA values 0.1 to 0.5%) [43]. Surprisingly, this did not lead to substantial changes in the estrogenic potency of the substances in the mouse uterine weight test.…”
Section: Development Of Hormonally Active [12-diarylethylenediamine]mentioning
confidence: 97%
“…As shown exemplarily for the meso derivative the in-vivo effect in the animals is based on a reduction of the endogenous estrogen level caused by an interference with the ovarian steroid biosynthesis. N-ethylated derivatives of these compounds did not display strong estrogenic properties indicating that variation of the type and position of the ring substituents is the better choice for optimization of the pharmacological properties [51]. Comparative studies with cisplatin indicated that the minor antiproliferative invitro activity is probably not due to a rapid inactivation of the compounds by bionucleophiles but rather to an insufficient accumulation in the cultured tumor cells and a steric hindrance of its 2,6-standing fluorine atoms during the interaction with the DNA [50].…”
Section: Development Of Hormonally Active [12-diarylethylenediamine]mentioning
confidence: 99%
“…Ligands such as estrogen analogues [142], amino acids [143], tryptamine [143], berenil [144], sugars [145], and ferrocene [146] have also been utilized for specific targeting. Recently, novel platinum complexes containing Cantharidinbased bioactive ligands [147] Fig.…”
Section: Platinum Complexes Bearing Biologically Active Ligandsmentioning
confidence: 99%
“…Apart from its decreasing the endogenous level of testosterone to values comparable with those after orchiectomy it does not possess sufficient Ptbased cytotoxicity or ER-mediated antitumour activity like meso-26. Partly in continuation of these studies, Gust et al investigated the stereochemical implications and preconditions for the antitumoural activity of compounds 27 in ER + human MCF-7 breast cancer cells [71]. When they tried to increase the estrogenic and cytotoxic activities of meso-27 and D,L-27 by ethylation of the N-atom(s) they found that these two kinds of activity require different substituent patterns of the aromatic rings and different spatial structures of the five-membered chelate rings.…”
Section: Conjugates With Selective Estrogen Receptor Modulators (Serm)mentioning
confidence: 99%
“…(16). Estrogenic and non-estrogenic [1,2-diphenylethylenediamine]platinum(II) complexes 26 and 27 and their effects in tumour cells[67][68][69][70][71].…”
mentioning
confidence: 99%